Effect of the Nerve Growth Factor Mimetic GK-2 on Brain Structural and Functional State in the Early Postresuscitation Period - M. Sh. Avrushchenko; Yu.V. Zarzhetsky; V. V. Moroz; I. V. Ostrova; T. A. Gudasheva; S. B. Seredenin (Общая реаниматология, 2012)
Objective: to evaluate the efficacy of the nerve growth factor mimetic GK-2 used to improve the structural and functional state of the brain in the early postresuscitation period. Material and methods. Cardiac arrest was induced in mature male albino rats for 12 minutes, followed by resuscitation. The neurological state of the resuscitated animals was assessed by a scoring scale. On postresuscitation day 7, the density and composition of neuronal populations of Purkinje cells in the lateral cerebellar region and pyramidal neurons in the hippocampal CA1 sector were determined by a differential morphometric analysis. The results were statistically processed using the ANOVA method. Results. The use of GK-2 was found to accelerate neurological recovery in the resuscitated animals. On day 7 after 12-minute cardiac arrest, the resuscitated animals showed neuronal dystrophic changes and death in the neuronal populations highly susceptible to ischemia. It was shown that the systemic administration of the nerve growth factor mimetic GK-2 contributed to a reduction in the magnitude and depth of postresuscitation changes in the cerebellar Purkinje cells and prevented dystrophic changes in the pyramidal cells of the hippocampal CA1 sector. The findings suggest that GK-2 has a neuroprotective effect in the recovery period after total body ischemia. Conclusion. The results of this study indicate the efficiency of the systemic administration of the nerve growth factor mimetic GK-2 in improving the brain structural and functional state in the early postresuscitation period. This determines perspectives for the use of GK-2 to prevent and correct posthypoxic encephalopathies. Key words: the nerve growth factor mimetic GK-2, postresuscitation period, neuronal dystrophic changes and death, neurological status.